ANAPHORIC REFERENCE IN JUSTIN BIEBER’S ALBUM “BELIEVE ACOUSTIC” - Hisarmauli Desi Natalina Situmorang; Muhammad Natsir (State University of Medan, 2014)
ABSTRACT This research focused on anaphoric reference used in Justin Bieber’s Album “Believe Acoustic”. The research conducted by using descriptive qualitative method. The data was collected from the Justin Bieber’s album “Believe Acoustic”. The finding of the thesis show that there are 64 lines (sentence, phrase) that consist of 3 anaphoric reference which are anaphora (10), cataphora (6), and zero anaphora (48). The most dominant types is zero anaphora, which means the writer want to create an implicitly lyric and has a deep meaning as well. Key words: anaphoric reference, album, lyric.